Specters in the glass house - Wright, Jaime Jo (Bethany House, a division of Baker Publishing Group, 2024)
"In 1921, heiress Marian Arnold begins having nightmarish visions in her family's butterfly house, but when she finds a body, she must separate her imaginings from reality. A century later, Remmy Shaw joins a memoir writer to research Marian's connection to the "Butterfly Butcher," only for the specter of the past to rise again"--